2008
DOI: 10.1002/pssb.200743532
|View full text |Cite
|
Sign up to set email alerts
|

The band structure of a layered Hg3TeCl4 crystal formed by energy states of HgCl2 and HgTe crystals

Abstract: The ab‐initio calculated band structure of a not as yet investigated orthorhombic Hg3TeCl4 crystal (Pbca, D152h) was analyzed by means of the elementary energy‐bands concept. It was demonstrated that this band structure originates from that of a layered HgCl2 dielectric deformed by the presence of the HgTe structural elements. Further, it was revealed that the valence band of Hg3TeCl4 is composed of the 8‐branch elementary energy bands corresponding to the actual Wyckoff position c (x, y, z) of D152h group tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Mechanical properties of the crystal as well as the X-ray investigations point to its layered properties, there are 64 atoms in the unit cell which are arranged into two double, translationally non-equivalent layers perpendicular to the y axis. It was shown that the anisotropy of the overlap of electron wave functions is different in various energy ranges and leads to the Davydov splittings in the band structure, in particular in the Γ point of the conduction band [2,3]. Hence, the anisotropy of the electron and hole effective masses does not correspond to the mechanical anisotropy of the crystal and it is not typical for layered crystals (m 2 (hν) dependence points to the presence of the direct optical transitions in the crystal which is in agreement with the theoretical band structure calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical properties of the crystal as well as the X-ray investigations point to its layered properties, there are 64 atoms in the unit cell which are arranged into two double, translationally non-equivalent layers perpendicular to the y axis. It was shown that the anisotropy of the overlap of electron wave functions is different in various energy ranges and leads to the Davydov splittings in the band structure, in particular in the Γ point of the conduction band [2,3]. Hence, the anisotropy of the electron and hole effective masses does not correspond to the mechanical anisotropy of the crystal and it is not typical for layered crystals (m 2 (hν) dependence points to the presence of the direct optical transitions in the crystal which is in agreement with the theoretical band structure calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Properties of this crystal have been not investigated experimentally so far, except its crystalline structure [1]. From the ab initio band structure calculations within a framework of density functional theory (DFT) follows that Hg 3 TeCl 4 is a wide band-gap layered photoelectric with a smallest band gap located in the Γ point of the Brillouin zone [2]. Hence, a characteristic dependence of the absorption coefficient α on hν as well as the inter-band photoluminescence should be expected for this crystal.…”
Section: Introductionmentioning
confidence: 99%
“…This sequence will be further used to explain the topology of the 8-branch EEBs and their separation into two 4-branch EEBs in a given energy range. The obtained picture of the Davydov splitting in the EEBs in the BZ will be verified with the numerical band-structure calculation results of the D (Pbca) space group describing the symmetry of the crystal, and the presence of two double, translationally nonequivalent atomic layers in the unit cell, perpendicular to the y-axis [1]. The space group describing the symmetry of the double atomic layer is…”
Section: Hmentioning
confidence: 96%
“…It has been shown that the anisotropy of the valence-band top and the conduction-band bottom as well as of the effective masses of charge carriers do not correspond to the mechanical anisotropy of this crystal [1]. Further, it was shown that the valence band is composed of some of the smallest building parts, the so-called elementary energy bands (EEBs) [2][3][4] which, in the case of 3 4 Hg TeCl , consist of 8 branches.…”
Section: Hmentioning
confidence: 97%
See 1 more Smart Citation